A Rare non-auto immunodeficiency disease (AIDS) related neo-plasm Kaposi sarcoma in Iraqi man: a case report - Al-Helfi, Haider; Al-Saad, Rasha; Al-Shewered, Ahmed (International Journal of Medicine, 2015)
The aim of this article is to report unusual case of KS presenting in the patient with negative serology for AIDS. Kaposi Sarcoma (KS) is a rare entity. It is a vascular neoplasm mainly affecting the skin of the lower extremities. Although it is the most common neoplasm affecting patients with AIDS, sporadic cases in HIV-negative people have been reported but it is rare.Â  Here, we present a case of a non-auto immunodeficiency disease (AIDS) related KS. A 72 year-old male, Iraqi patient presented to our oncology outpatientâ€™s unit in Al-Shafaa Oncology Center with multiple subcutaneous nodules. The diagnosis was based on histopathological and immunohistochemical analysis of the excised lesion, serology tests and imaging investigations. The patient had a 13-month history of a slowly progressing pigmented multiple lesions on the lower and upper extremities. The patient had visceromegaly as splenomegaly at the time of presentation. His serum was negative for the common types of viral infections including Human Immunodeficiency Virus (HIV) on routine serology. On general examination, the man look well, no pallor, no fever, no cachexia present and no jaundice. There are a multiple ill defined, irregular hyper-pigmented nodules to plaques were present on forearm, legs, feet and hands. The nodules and plaque was firm in consistency and was non-tender. The lesions were deep reddish to brownish in color. The size of the lesions were arranged from 0.5-1.5 cm. No scaling was evident. The patient was under treatment with chemotherapeutic regimen of Paclitaxel.Â